Father and God (the Father) in Wiesel’s Night as Response to the Holocaust - Shannon Quigley (Humanities, 2021)
The proposed paper will begin by looking at the father–son relationship in Elie Wiesel’s Night. I will then briefly note the father–child relationship between God and Israel in the prophets of the Hebrew Bible. I will link the two challenges evident in Wiesel’s Night and in his continuing thought after the Shoah—the loss of family and the loss of God, his faith and/or his understanding of God—and note how these affect one another. After further assessing Wiesel’s father imagery in Night, I will note how Wiesel’s story, eventually making its way into the current version of Night, played a critical role in affecting the thought of Christian leaders and post-Holocaust Jewish–Christian reconciliation efforts.